Pendidikan dan Konflik (Potret Konflik Sunni-Syiah dan Imbasnya Terhadap Pendidikan di Bangil Kabupaten Pasuruan) - Muhammad Andi Isya' (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
The conflict between Sunni and Shia has taken place from the very beginning of the two ideologies. The eternal conflict between the Sunni and the Shias enters into the strategic domains of the moral formation of children, namely education. Education is a strategic place in the formation and cadre of a child. Original education is expected to be the formation of a neutral personality, more often ridden with certain ideologies so that the child's personality is formed from Islamic education in accordance with the ideology of an educational institution. The purpose of this research is to know how far conflict sekmetian Sunni and Shia and its impact to education world especially in District of Bangil Pasuruan Regency. This research uses qualitative approach with fenomelogical perspective. The data were collected through in-depth interviews, participatory observation and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing. From the results of this study obtained the conclusion that the conflict that stood for years can stick again when the trigger is punctured. As a result education is a disadvantaged element in this sectarian conflict. Education that should be neutral, polluted and polarized by the divisive elements. In addition, education contributes to polishing and beautifying the conflict between Sunnis and Shiites. Conflicts that occurred have entered the realm of education. A deep understanding of the teachings of affection between fellow Muslims, supported by an unbalanced curriculum of Islamic education and an educator who is not blind fanaticism, will be the solution to the realization of peace for both sects.